Propriedades fisícas e mecânicas de resinas compostas convencionais e bulk fill – efeito da composição e do modo de fotoativação - Barcelos, Luciana Mendes (2020)
Resins composites have become the first choice for direct restorations for anterior and posterior teeth. The great popularity for the use of these materials is related to the aesthetic appearance and the possibility of less invasive procedure, reducing the need of removal of healthy tissues. Resins composite also enable coronary reconstruction, promoting rehabilitation and aesthetics in a more accessible way. The performance of resin composites can be influenced by several factors, such as biological, mechanical and aesthetic. The general objective of this study was to evaluate characteristics inherent to materials that can interfere with the polimerization. Three objectives are part of this study; specific objective 1: to investigate the influence of the photoinitiator system on the polymerization kinetics of methacrylamide-based monomers as an alternative to methacrylars in adhesives of dental materials; specific objective 2: to develop a laboratory device for standardization of radiographs using conventional films and digital sensors, validating it through radiopacity analysis of composite resins; specific objective 3: to evaluate the effect of single spectrum or multi-spectrum light sources on the mechanical properties expressed by Knoop hardness, degree of conversion and modulus of elasticity of conventional and bulk fill resins composite with different photoinitiators systems. In conclusion, polymerization kinetics was affected by photoinitiators for both monomers tested. Viscosity increased significantly with the incorporation of secondary methacrylamide. This work demonstrated the viability of using newly synthesized methacrylamide monomers in conjunction with primer systems already used in commercial materials. Conventional and bulk fill resins composite exhibited adequate radiopacity level. The digital radiographic methods and imaging processes tested showed similarity classification capacity for all resins composite tested. The developed device was able to standardize the radiographic methods used to evaluate the radiopacity of restorative materials. The composite resins Vittra APS, Opus Bulk Fill APS and Tetric Evoceram Bulk Fill showed adequate values of Knoop hardness, conversion gradu and modulus of elasticity in the analyses performed on the surface and at the depth of 2.0mm. The Light Sources Bluephase and VALO Cordless resulted in higher values of Knoop hardness, degree of conversion and modulus of elasticity when compared to the sources independent of the tested resin. The photoinitiator system tends to influence the results less than the performance of light sources.